2017
DOI: 10.1093/mnras/stx656
|View full text |Cite
|
Sign up to set email alerts
|

Searching for pulsars associated with the Fermi GeV excess

Abstract: The Fermi Large Area Telescope has detected an extended region of GeV emission toward the Galactic Center that is currently thought to be powered by dark matter annihilation or a population of young and/or millisecond pulsars. In a test of the pulsar hypothesis, we have carried out an initial search of a 20 deg 2 area centered on the peak of the galactic center GeV excess. Candidate pulsars were identified as a compact, steep spectrum continuum radio source on interferometric images and followed with targeted … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 55 publications
(77 reference statements)
0
16
0
Order By: Relevance
“…Some other notable cases where prior information about the steep spectrum assisted the pulsar discovery are: PSR J2022+3842, the central source of supernova remnant G76.9+1.0, concurrently detected in radio imaging and time-domain by Marthi et al (2011), independently from the X-ray discovery by Arzoumanian et al (2011); and PSR J0815+4611, which was first identified as a point source in the deep epoch-of-reionization observations of the 3C196 field and turned out to be a highly polarized nearby pulsar (Kondratiev et al, private communication) 3 . More recently, image-based maan@astron.nl 1 Astronomical Institute "Anton Pannekoek", University of Amsterdam, Science Park 904, 1098 XH Amsterdam, The Netherlands 2 Radio Astronomy Centre, NCRA-TIFR, Udagamandalam, India 3 See http://www.astron.nl/dailyimage/main.php?date=20150331 and http://www.astron.nl/lotaas/ searches utilizing steep-spectrum as one of the main criteria have uncovered 8 new pulsars from Fermi Large Area Telescope unidentified sources (Bhakta et al 2017;Frail et al 2018). These discoveries demonstrate the potential of spectral information based searches for radio pulsars, and motivate investigation of the steep spectrum sources for the presence of any pulsations.…”
Section: Introductionmentioning
confidence: 99%
“…Some other notable cases where prior information about the steep spectrum assisted the pulsar discovery are: PSR J2022+3842, the central source of supernova remnant G76.9+1.0, concurrently detected in radio imaging and time-domain by Marthi et al (2011), independently from the X-ray discovery by Arzoumanian et al (2011); and PSR J0815+4611, which was first identified as a point source in the deep epoch-of-reionization observations of the 3C196 field and turned out to be a highly polarized nearby pulsar (Kondratiev et al, private communication) 3 . More recently, image-based maan@astron.nl 1 Astronomical Institute "Anton Pannekoek", University of Amsterdam, Science Park 904, 1098 XH Amsterdam, The Netherlands 2 Radio Astronomy Centre, NCRA-TIFR, Udagamandalam, India 3 See http://www.astron.nl/dailyimage/main.php?date=20150331 and http://www.astron.nl/lotaas/ searches utilizing steep-spectrum as one of the main criteria have uncovered 8 new pulsars from Fermi Large Area Telescope unidentified sources (Bhakta et al 2017;Frail et al 2018). These discoveries demonstrate the potential of spectral information based searches for radio pulsars, and motivate investigation of the steep spectrum sources for the presence of any pulsations.…”
Section: Introductionmentioning
confidence: 99%
“…The compact, steep spectrum, polarized radio sources, identified toward 4C 21.53 and M28 (Rickard & Cronyn 1979;Erickson 1980;Hamilton et al 1985;Erickson et al 1987) led to the discovery of the first isolated millisecond pulsar PSR B1937+21 (Backer et al 1982) and the first globular cluster millisecond pulsar PSR B1821−24 (Lyne et al 1987), respectively. Small numbers of radio pulsars continue to be discovered by targeting pulsations searches toward compact, steep spectrum (polarized) radio sources identified through interferometric imaging (Navarro et al 1995;Strom 1987;Bhakta et al 2017;Frail et al 2018;Kaplan et al 2019). Increasingly however, these imagebased surveys are finding large numbers of compelling candidates (Kaplan et al 2000;Crawford et al 2000;De Breuck et al 2000;de Gasperin et al 2018) in which pulsation searches have been unsuccessful (Roshi & Ransom 2012;Schmidt et al 2013;Maan et al 2018;Hyman et al 2019;Straal & van Leeuwen 2019;Crawford et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In our current GC work we have been focused on exploring the radio spectral domain, looking to identify compact, steep spectrum radio sources near the GC or within the bulge. Several different approaches have been taken to identify such sources, including imaging a 5 deg 2 region centered on Sgr A* (Hyman et al 2019), comparing existing large-scale meter and centimeter radio surveys (Bhakta et al 2017;de Gasperin et al 2018) and targeted imaging of the error ellipses of unidentified Fermi sources. Pulsars are the conventional source population expected to be compact and steep spectrum (Bates et al 2013;Maron et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…With the ongoing development of hybrid strategies to infer the actual number of MSPs from Fermi data (Bartels et al 2016;Bhakta et al 2017) and with future radio observations with the square kilometer array (SKA) it may be possible to detect MSPs directly and map out their distribution in the MW inner 10 pc (Dewdney et al 2009;Macquart & Kanekar 2015;Brandt & Kocsis 2015;Calore et al 2016), as recently suggested by Abbate et al (2017).…”
Section: Controversy Of the Msp Origin Of The Fermi Excessmentioning
confidence: 99%